You are on page 1of 4

# 1.

x+ =

xy2+x=2y

[xy2+x] = [2y]

[y2x] +
[x]= 2 [y]

[y2] x + y2 [x] + 1 = 2y

2y [y] x + 1 y2 + 1 = 2y

2y yx + y2 + 1 = 2y
2y y x + y2 + 1= 2y
Simplificamos:

2xyy + y2 + 1 = 2y
Simplificamos:

y (2xy + y) + 1= 2y
Resolver la ecuacin por y:

+
Solucin del sistema: =

2. = +

## 3x2 y=y2 +2x2

[3x3 y]= [y2 +2x2]

3 [yx3]=2 [x2] + [y2]

3 ( [y] x3 + y [x3])= 2 2x + 2y [y]

## 3(yx3 + 3x2 y)= 4x + 2yy

3 (yx3 +3yx2)= 4x + 2yy
Simplificamos:

Simplificamos:

## 3x2 (xy + 3y) = 2(yy + 2x)

Resolver la ecuacin por y:

Solucin del sistema: =

3. ( + )

=

xy (y + 4x) = y 2x

[xy (y + 4x)] = [y 2x]

## [y] x (4x+y) + y [x] (4x+y) + yx [4x+y] = [y] 2 [x]

yx (4x + y) + 1y (4x + y) + (4 [x]+ [y]) yx = y 2 1

## yx (4x + y) + y (4x + y) + (41 + y) yx = y 2

yx (4x + y) + y (4x + y) + y (y + 4) x = y 2
Simplificamos:

Xy (y + 4) + x (y + 4x) y + y (y + 4x) = y 2
Simplificamos:

2x (y + 2x) y + y2 + 8xy = y 2
Resolver la ecuacin por y:

+ +
=
+
( )
4. =
( )
( )
=
( )

[xy] = [y (2x3 y3) x (2x3 3y3)]

## [y] x + y [x] = x (2x3 3y3) [y (2x3y3)] [x (2x3 3y3)]

y (2x3 y3) (x(2x3 3y3))2

yx + 1y = ( [y] (2x3 y3) + y [2x3 y3]) x (2x3 3y3) ( [x]

(2x33y3) + x [2x3 3y3]) y (2x3 y3) x2 (2x3 3y3)2

yx + y = x (2x3 3y3)(y (2x3 y3) + (2 [x3] [y3])y) y(2x3

y3)(1(2x 3y ) + (2
3 3
[x3] 3 [y3]) x) x2 (2x3 3y3)2

yx + y = x (2x3 3y3) (y(2x3 y3) + (2 3x2 3y2 [y])y) y(2x3

y3)(2x3 + (2 3x2 3 3y2 [y])x 3y3) x2 (2x3 3y3)2

## yx +y = x(2x3 3y3)(y(2x3 y3) + y(6x2 3yy2)) y(2x3 y3)(2x3 +

x(6x2 9yy2) 3y3) x2 (2x3 3y3)2
yx + y= x(2x3 3y3)(y(2x3 y3) + y(6x2 3y2 y)) y(2x3 y3)(2x3 +
x(6x2 9y2 y) 3y3) x2 (2x3 3y3)2
xy + y= y(6x2 3y2 y) x (2x3 3y3) y(2x3 y3)(6x3 9y2 y) x (2x3
3y3)2 + (2x3 y3) yx (2x3 3y3) y(2x3 y3) x2 (2x3 3y3)
Simplificamos:

## xy + y = (3y6 + 4x3 y3 + 4x6) (xy y) x2 (3y3 2x3)2

Resolver la ecuacin por y:

+ +
+
( )
=
+ +

( )
5. ( + ) =

6. ( ) + ( + ) =

7. ( + ) =

8. . =

9. (
+ ) =

10. ( ) + . =

+
11. = ( + )

(+ )
12. = +

13. ( ) ( ) =

+/
14. =

15. ( ) + ( ) =

16. ( ) ( + ) =

17. =

18. = +